Examining professional competencies for emerging and novice social workers in health care. (3rd July 2019) - Nicholas, David B.; Jones, Catherine; McPherson, Barbara; Hilsen, Leeann; Moran, Jennifer; Mielke, Kent
ABSTRACT: This participatory project identified competencies of social workers in health care, with a focus on entry to the field. Findings reflected discussion groups with n = 24 social workers in health care settings. Identified core competencies were: (a) a core base of knowledge specific to social work in health care, (b) understanding of the health care system and implications for practice, (c) a strong work ethic and confidence working with limited supervision, (d) interpersonal skills for multi-disciplinary teamwork, (e) understanding about complex role and power dynamics, (f) accountability for one's own work/practice and commitment to professional development, (g) reflectiveness on practice, and (h) an organizational commitment to capacity building.